Nano-technological advancements in multimodal diagnosis and treatment - Dinesh Bhatia; Tania Acharjee; Shruti Shukla; Monika Bhatia (AIMS Biophysics)
Nanomedicine, which is blazing new trails in modern healthcare, exploits the distinctive attributes of nanoparticles (NPs) to reimagine diagnosis and therapy. With imaging, this “magic ammunition” enhances the capability of MRI, a noninvasive, high-resolution technology that can pinpoint cancers with astonishing precision. Unlike traditional treatments, which muddle the distinction between diseased and healthy tissue, gold nanoparticles (AuNPs) directly target tumors, using increased permeability and retention (EPR) effects for crystal-clear, early-stage detection. While gadolinium (Gd (III)) T1 agents are the most widely used in clinical practice, iron oxide T2 agents have fallen out of favor due to failing to perform. Beyond imaging, NPs offer a “one-two punch” in the treatment of complicated disorders by enabling photothermal (PTT), photodynamic (PDT), and multimodal therapies (MMT), as well as nano drug delivery systems (NDDS). This nanotechnology-based technique personalizes medicines for diseases such as tuberculosis (TB) and cardiovascular disease (CVD), focusing on damaged tissues to improve therapeutic response. In tuberculosis, NPs circumvent medication resistance by delivering medicines directly to infected cells, thus avoiding biological barriers that impede standard treatments. Similarly, in CVD, NPs target arterial plaques to improve treatment accuracy while reducing systemic adverse effects. Furthermore, the genomic “blueprint” is evolving parallel to nanotechnology, with India's “Genome India” initiative mapping 10,000 genomes, lighting the path for genetic chips suited for specific disorders and moment tests. The convergence of nanotechnology and genomes is an arcade modification, bringing accuracy and personalization to the forefront of cancer and tuberculosis treatment.